Servicescape and Service Quality in Creating Customer Loyalty - Aldina Shiratina; Adnan Rajak; Yanto Ramli; Nuri Putria Nirba Nirwana (Yayasan Ilomata, 2021)
The development of cooperatives is currently starting to stagnate. This study aims to reveal this research. This research aims to analyze the effect of Servicescape on customer loyalty, the impact of Servicescape on service quality, the impact of service quality on customer loyalty, and the impact of Servicescape on customer loyalty mediated by service quality. This research uses a quantitative method approach. The unit of analysis in this study was all female members of the Padalarang Partnership Village Cooperative in 2016, totaling 125 people consisting of active and passive female members. The population in this study amounted to 125 people and a set precision or a significance level of 0.05, so the sample size in this study was 95 members as respondents. This study was analyzed using multiple linear regression for verification analysis. The findings in this study are Servicescape affects service quality, service quality affects the loyalty of female members, and Servicescape affects the loyalty of female members.